The Advent of CAR T-Cell Therapy for Lymphoproliferative Neoplasms: Integrating Research Into Clinical Practice - Cerrano, Marco; Ruella, Marco; Perales, Miguel-Angel; Vitale, Candida; Faraci, Danilo Giuseppe; Giaccone, Luisa; Coscia, Marta; Maloy, Molly; Sanchez-Escamilla, Miriam; Elsabah, Hesham; Fadul, Afraa; Maffini, Enrico; et al. (Frontiers in Immunology, 2020)
Research on CAR T cells has achieved enormous progress in recent years. After the impressive results obtained in relapsed and refractory B-cell acute lymphoblastic leukemia and aggressive B-cell lymphomas, two constructs, tisagenlecleucel and axicabtagene ciloleucel, were approved by FDA. The role of CAR T cells in the treatment of B-cell disorders, however, is rapidly evolving. Ongoing clinical trials aim at comparing CAR T cells with standard treatment options and at evaluating their efficacy earlier in the disease course. The use of CAR T cells is still limited by the risk of relevant toxicities, most commonly cytokine release syndrome and neurotoxicity, whose management has nonetheless significantly improved. Some patients do not respond or relapse after treatment, either because of poor CAR T-cell expansion, lack of anti-tumor effects or after the loss of the target antigen on tumor cells. Investigators are trying to overcome these hurdles in many ways: by testing constructs which target different and/or multiple antigens or by improving CAR T-cell structure with additional functions and synergistic molecules. Alternative cell sources including allogeneic products (off-the-shelf CAR T cells), NK cells, and T cells obtained from induced pluripotent stem cells are also considered. Several trials are exploring the curative potential of CAR T cells in other malignancies, and recent data on multiple myeloma and chronic lymphocytic leukemia are encouraging. Given the likely expansion of CAR T-cell indications and their wider availability over time, more and more highly specialized clinical centers, with dedicated clinical units, will be required. Overall, the costs of these cell therapies will also play a role in the sustainability of many health care systems. This review will focus on the major clinical trials of CAR T cells in B-cell malignancies, including those leading to the first FDA approvals, and on the new settings in which these constructs are being tested. Besides, the most promising approaches to improve CAR T-cell efficacy and early data on alternative cell sources will be reviewed. Finally, we will discuss the challenges and the opportunities that are emerging with the advent of CAR T cells into clinical routine.